Maladministration in Indonesia's Interreligious Marriage - Asep Syarifuddin Hidayat (Jurnal Cita Hukum, 2023)
In Indonesia, the polemic on interfaith marriages has not yet ended, even though over time and the times. Even though the issue of interreligious Marriage has been handled and regulated in the Marriage Law, there are still many people who practice it. In Indonesia, interfaith marriages cause not only legal problems but also administrative ones. There are still exceptions to the Marriage Act that allow couples to marry across religions. Because according to positive Indonesian Law, Marriage is not equated with a simple genetic relationship. However, the administration must prove a legal relationship with the state, including the registration of marriages. The research method used is a qualitative research method with a literature approach. The results of the study state that there are still gaps and opportunities for maladministration in interfaith marriages. The behavior occurs in the form of apostasy or changing religions before Marriage, then changing beliefs after Marriage. This was done to get the legality of Marriage in the form of a marriage book. These maladministration opportunities must be closed and eliminated by making government regulations or giving strict sanctions to the perpetrators of maladministration. The sanctions are criminal or fines for people who carry out legal smuggling like this.